1999
DOI: 10.1007/s11664-999-0015-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of homo- and heteroepitaxial growth of SiC on α-SiC(0001) by solid-source molecular beam epitaxy

Abstract: Epitaxial growth of SiC on hexagonal (or α)-SiC(0001) has been performed by means of solid-source molecular beam epitaxy (MBE). The solid-source MBE growth conditions have been analyzed concerning the supersaturation and the excess phase formation of silicon and carbon. In general, our results demonstrate that control of the Si/C ratio and the supersaturation (S) is essential for the growth mode and the kind of polytype grown. Low temperature (T<1450K) deposition on on-axis SiC substrates always results in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Many twins T and stacking faults SF are visible in the image. This surface is the substrate for the next epitaxial layer [86]. For homo-epitaxy the same polytype crystal continues to grow and for hetero-epitaxy a new polytype will nucleate.…”
Section: Ipycmentioning
confidence: 99%
“…Many twins T and stacking faults SF are visible in the image. This surface is the substrate for the next epitaxial layer [86]. For homo-epitaxy the same polytype crystal continues to grow and for hetero-epitaxy a new polytype will nucleate.…”
Section: Ipycmentioning
confidence: 99%
“…The most serious problem in the growth of SiC heterostructures is the occurrence of incoherent twin ͑double-position͒ boundaries ͑DPB͒ when 3C-SiC is involved. Recently, we have already 6,8,9 shown that the growth of 3C-SiC can be significantly improved by an alternating supply of Si and C at medium T ͑1430 K͒ on on-axis ␣-SiC͑0001͒. diameter of DPB domains was found to be increased to some hundreds m. That already demonstrated the importance of adatom mobility and nucleation conditions for the growth of single domain 3C-SiC layers.…”
mentioning
confidence: 92%
“…Afterwards a SiC-buffer layer was grown via step flow at the same T and a carbon flux of 10 13 cm Ϫ2 s Ϫ1 , cor-responding to Rϭ7.5 nm/h, a rate low enough to prevent nucleation also on nominal on-axis substrates. 6,8 The final step morphology mostly consists of steps one unit cell in height.…”
mentioning
confidence: 99%
“…growth rate or purity. The temperature limitation has a direct impact on SiC polytype which can be grown by MBE so that 3C-SiC is most commonly obtained using this technique [58,59]. And this is what is happening when adding Ge to SiC growth by MBE [39,60].…”
Section: Increasing Ge Incorporationmentioning
confidence: 99%